In vitro evaluation of the physical characteristics and push-out bond strength of new experimental nano-MTA - Nada Omar; Yousra Aly; Haidy N. Salem (Bulletin of the National Research Centre)
Abstract Background This research assessed two materials to be used as endodontic sealing material. The setting time, pH change, calcium ions release, microhardness and push-out bond strength were compared. Methods In this in vitro experimental study, comparison was done between: one commercial perforation repair material MTA Angelus and experimental Nano-MTA. For each material, testing for setting time was done using Vicat apparatus, measurement of pH values was established by pH meter, the discharged calcium ions were measured at 1 day, 1 week and 4 weeks post setting via Spectro-photo-meter, three diagonal indentations were created at each specimen surface using Vickers hardness machine. Two groups (n = 10) of maxillary central incisors were used according to the type of root-end filling material. To determine the bond strength, the universal testing apparatus was used. The de-bonded specimens were examined under the stereo-microscope to assess fracture mode. Results Nano-MTA and MTA angelus were similar in pH change, setting time and push-out strength records. The nano-MTA group showed significantly higher microhardness and Ca ion release. Conclusions Under the parameters of the current investigation, we can conclude that the physical properties of Nano-MTA and commercially available MTA cement (MTA-Angelus) are comparable. Nano-MTA showed higher hardness properties and higher Ca ions release than MTA-Angelus, which could be considered as a potential property to be used as a dentin repair and root-end filling material.